1997
DOI: 10.1143/jjap.36.3374
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength Measurement of Silicon Chips

Abstract: In this study, a three point bending test is used to determine how the susceptivity of large chips to brittle fracture correlates with chip thickness and backend process quality. Four sets of wafer backend processes, including the commonly used mechanical grinding, were used in this experimental work. In the mechanical grinding process, chip strength was more significantly influenced by the geometry of the machine mark than by the depth of the scratched groove. This experimental result indicates that a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In 1997, Lee et al showed that the direction of the grinding marks had a dominating effect on the chip strength values when the chip was loaded with three-point bending loads. They also observed that additional treatments involving polishing, chemical wet etching, and plasma etching enhanced chip strength [3]. The wafer they used were 150 mm in diameter.…”
Section: Introductionmentioning
confidence: 96%
“…In 1997, Lee et al showed that the direction of the grinding marks had a dominating effect on the chip strength values when the chip was loaded with three-point bending loads. They also observed that additional treatments involving polishing, chemical wet etching, and plasma etching enhanced chip strength [3]. The wafer they used were 150 mm in diameter.…”
Section: Introductionmentioning
confidence: 96%
“…The silicon strength measurement by three-point bending test has been thoroughly investigated and proved to be suitable and efficient [3][4][5]. The measurement of ultimate tensile strength of silicon chips was investigated by some researchers in the past.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Lee et al showed that the grinding marks had a strong adverse effect on the chip strength when the chip was loaded in a three-point bending test. 1) Chemical mechanical polishing (CMP) and rapid thermal annealing (RTA) are frequently performed on silicon wafers during device manufacturing, and these two processes are known to degrade the mechanical strength of wafers. 2,3) Also, the strength of a silicon wafer depends heavily on the design of the wafer edge shape before the stress is induced on the surface of the film.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) Few studies, however, have investigated the relationship between mechanical strength and the edge profile of wafers. In this study, wafers with different edge profiles were tested using a mechanical drop test 1) and an optical image analyzer to compare the impact of the wafer edge design on the breakage ratio. Information concerning the number of broken wafers was collected in-line during manufacturing.…”
Section: Introductionmentioning
confidence: 99%